Linear extensions of dynamical systems on a torus that possess Green-Samoilenko functions - Wojtowicz, B.; Kulik, V. L. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
By using Lyapunov functions with alternating signs, we study problems of regularity and weak regularity for some linear extensions of dynamical systems on a torus.